Do Australian Children have more problems today than twenty years ago? - Smart, D; Sanson, A (My University, 2008)
The popular view that today's Australian children are faring worse than those of yesteryear can be investigated by comparing similar studies from now and from 20 years ago. Growing Up in Australia, the Longitudinal Study of Australian Children (LSAC) follows two cohorts - infants, born 2003-2004, and preschool children, born 1999-2000. The Australian Temperament Project (ATP), still running today, began in 1983 with a cohort of Victorian infants, born 1982-1983. These two studies feature parallel data on temperament and behaviour, collected by teachers and parents. The findings indicate that the majority of both sets of children are developing well. Some differences between the two cohorts were found as reported by parents and teachers. The authors discuss the results and methodological differences, which could reflect awareness or tolerance of behaviour problems by parents and teachers, and changes in school and home environments.
Keywords: Children; Childhood and child development; Children; Childhood and child development